2003
DOI: 10.1016/s0014-5793(03)00748-8
|View full text |Cite
|
Sign up to set email alerts
|

Domain architecture of the polyglutamine protein ataxin‐3: a globular domain followed by a flexible tail

Abstract: Anomalous expansion of a polyglutamine (polyQ) tract in the protein ataxin-3 causes spinocerebellar ataxia type 3, an autosomal dominant neurodegenerative disease. Very little is known about the structure and the function of ataxin-3, although this information would undoubtedly help to understand why the expanded protein forms insoluble nuclear aggregates and causes neuronal cell death. With the aim of establishing the domain architecture of ataxin-3 and the role of the polyQ tract within the protein context, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 23 publications
7
107
1
Order By: Relevance
“…To date, the only studies on the structure of a full-length (or nearly full-length) poly-Q disease protein are for ataxin-3, which causes spinocerebellar ataxia 3 or Machado-Joseph's disease. The poly-Q repeat was found to be flexible and solvent exposed (Masino et al 2003) and expansion of the repeat from Q27 to Q78 resulted in reduced a-helix content and formation of b-sheet fibrils (Bevivino & Loll 2001). However, Chow et al (2004) found no major differences in secondary structure content for ataxin-3 with 15, 28 or 50 glutamines.…”
Section: Introductionmentioning
confidence: 94%
“…To date, the only studies on the structure of a full-length (or nearly full-length) poly-Q disease protein are for ataxin-3, which causes spinocerebellar ataxia 3 or Machado-Joseph's disease. The poly-Q repeat was found to be flexible and solvent exposed (Masino et al 2003) and expansion of the repeat from Q27 to Q78 resulted in reduced a-helix content and formation of b-sheet fibrils (Bevivino & Loll 2001). However, Chow et al (2004) found no major differences in secondary structure content for ataxin-3 with 15, 28 or 50 glutamines.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast to myoglobin, the polyglutamine expansion within a different model protein, CI2, was found to have no significant effect on the equilibrium and kinetic folding and unfolding transitions of the protein (39). Interestingly, the engineered polyglutamine tract in CI2 was located in a mobile loop linking two domains, which could be roughly likened to the case of ataxin-3, in which the polyglutamine-containing portion of the protein is believed to be a flexible solvent-exposed domain, in contrast to the folded N-terminal Josephin domain (40,41). On the other hand, in the myoglobin model (22), although a flexible loop was also targeted for polyglutamine insertion, the entire protein functions as a single domain.…”
Section: Kinetic Analysis Of Acid-induced Denaturation Of Ataxin-3-mentioning
confidence: 99%
“…A powerful approach to achieve it may be to identify the structural motifs involved in the interactions formed by ataxin-3 with other partners and to characterize further their structure and function(s). As a first step toward this aim, we have recently established the domain architecture of ataxin-3 and shown that it consists of an N-terminal globular domain with significant helical content, which spans the Josephin motif, and a flexible C-terminal tail containing up to three UIMs and the polyQ tract (10). Both our analysis and other indirect evidence strongly suggest that Josephin is an important functional region of ataxin-3 that plays a role both in the normal and the pathological functions of the protein.…”
mentioning
confidence: 99%